IMPLEMENTASI MODEL DISCOVERY LEARNING TERHADAP ATTITUDE TOWARDS CHEMISTRY (ATC) DAN HASIL BELAJAR SISWA - Makarawung, Angga Anugrah; Saiya, Abdon; Tuerah, Jeanne M. (SOSCIED, 2024)
This research is intended to examine Attitude Towards Chemistry and student learning outcomes from the implementation of Discovery Learning model in Chemistry learning at Rex Mundi Catholic High School Manado. The purpose of this study was to determine the implementation of discovery learning model towards ATC and students' learning outcomes in chemistry learning. This research used pre-experiment research design, namely One group pretest-posttest. The research was conducted at Rex Mundi Catholic High School Manado in class X with a sample size of 30 students. Data collection was done by using ATC questionnaire and multiple choice test instrument and data analysis was done by using normality test as prerequisite test, t-test, and n-gain score. The results of data analysis for hypothesis testing showed a significant difference in ATC and student learning outcomes before and after learning with the discovery learning model. Based on statistical testing, the results of hypothesis testing of ATC and student chemistry learning outcomes were obtained, namely tcalculate, ATC =156.10 > ttable=1.699 Sig value. 0.00 and tcalculate,Posttest =63.96 > t table=1.699 Sig value. 0,00. So that from hypothesis testing it can be concluded that there are differences in ATC and student chemistry learning outcomes before and after chemistry teaching with the discovery learning model. The results of data analysis for the n-gain test showed that the average n-gain value of ATC was 61.82% and the n-gain of learning outcomes was 73.5%, including in the moderately effective category. So it can be stated that the implementation of the discovery learning model is effective.